IDEOLOGI CULTUR DESAIN PAPAN IKLAN PADA RUANG PUBLIK TERBUKA DI KOTA KUPANG - Karus Margaretha; Semuel Hajai Nitbani; Karolus Budiman Jama; I Ketut Sutarwiyasa (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
East Nusa Tenggara is rich in local wisdom spread across several islands and regencies/cities in government administration. The city of Kupang is administratively-geographically located near the center of the provincial government. The logical consequence of the position of this administrative area is the proliferation of technological developments which have implications in various aspects of life. One that is clearly visible is the visual design of the advertisements displayed in every open public space. Visible ad designs tend to use visual displays that contain popular culture. This leads to the sinking of the existence of the local image owned by the people of East Nusa Tenggara. Through a descriptive-qualitative method with a phenomenological approach, this study seeks to reveal elements of ideology and culture in the design of billboards in open public spaces in Kupang City. Within the framework of the Semiotics theory, the local image becomes the object to be analyzed. The product produced in this research is documentation of local image visualization.